Determinants of farmers' awareness of climate change. Issue 3 (3rd July 2019) - Mustafa, Ghulam; Latif, Ismail Abd; Bashir, Muhammad Khalid; Shamsudin, Mad Nasir; Daud, Wan Mohamed Noordin Wan
ABSTRACT: Studies have found that farmers' awareness of climatic variations is the preliminary step for adaptation and mitigation in agriculture. Thus, the main aim of this article is to investigate the determinants of farmers' awareness of climate change. A multistage random sampling technique was used to collect primary data from Central and Southern Punjab, Pakistan through a structured questionnaire. Descriptive statistics were used to indicate the farmers' awareness level of climate change, whereas the binary logit model was applied to determine the factors affecting the farmers' level of awareness. The results showed that farmers were aware of prevailing temperature and rainfall patterns, but there is still a considerable potential for public perception to be shaped by relevant stakeholders. Further, it was found that farmers' level of awareness is determined by the environmental communication network, such as socioeconomic, institutional, and geographic factors.